Influencing Change: When “Best Practice” Changes and the Prototypical Good Farmer Turns Bad - Green, Laura; Kaler, Jasmeet; Liu, Nicola; Ferguson, Eamonn (Frontiers in Veterinary Science, 2020)
Twenty-nine farmers with a flock prevalence of lameness >5% agreed to participate in a longitudinal trial on treatment of lameness. They were identified from 1300 respondents to a questionnaire on management of, and attitudes towards, lameness in sheep. Farmers were visited once in 2013 and participated in a facilitated discussion around their treatment of lameness, in particular footrot, and the evidence-based new ‘best practice’. One year later the farmers were revisited and re-interviewed to investigate which managements they had changed, what had motivated the change and how they would persuade other farmers to adopt the current ‘best practice’. Overall lameness prevalence reduced from 7.6% to 4.3% between 2013 and 2014. The major changes were a reduction in foot trimming and an increase in use of antibacterials to treat footrot, and treating lame sheep within a week of onset of lameness. One farmer continued to practise foot trimming to treat lame sheep and reported an increase in prevalence of lameness from 15% in 2013 to 25% in 2014. At first interview most participants were resigned to having lame sheep. They believed that prototypical ‘good farmers’ (including trusted family members such as parents and grandparents who had taught them how to treat lame sheep) practised foot trimming, the traditional ‘best practice’. Participants considered that the new ‘best practice’ would be expensive and time consuming. In 2014, participants reported that factors that had influenced change were increased knowledge of the best evidence-base for treatment of lameness, trust in the facilitator to try some of the changes recommended and talking to other farmers who had already adopted the new ‘best practice’. Persistent change occurred because participants observed the health benefits of new ‘best practice’ for their sheep and that the new ‘best practice’ had saved time and money. Participants stated that other farmers would be convinced to change to new ‘best practice’ because it saved time and money, an example of cognitive dissonance; some felt that case studies in farming press would influence change but others considered that only one-to-one meetings would persuade farmers to adopt the new ‘best practice’.